FINANCIAL TECHNOLOGY TERDAFTAR SEBAGAI ALTERNATIF PINJAMAN MODAL USAHA BAGI MASYARAKAT - KH K, A RAHMAN (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2025)
Business capital is often a fundamental issue faced by individuals wanting to start small and medium-sized enterprises. Many home-based industries also struggle with capital, which can be difficult to obtain. Applying for a loan from banks requires collateral, and is compounded by high interest rates and other challenging requirements and procedures. The emergence of financial technology companies, or fintech, offers an alternative for business capital loans without collateral. Fintech is a type of company in the financial services sector combined with technology. The presence of legal regulations related to registered fintech companies can provide legal certainty for small and medium-sized enterprise (SME) operators. This situation indicates that public awareness of registered financial technology is still minimal, which can lead to significant losses for those seeking capital through unregistered financial technology, particularly for those in need of business capital. This study uses lectures and discussions targeted at the community of Sumur Batu Village, Teluk Betung Utara District, Bandar Lampung City, with the hope that the community will understand registered financial technology companies as a safe and legally certain alternative for business capital loans.